Coping with a Nuclearizing Iran - Dobbins, James (RAND Corporation, 2011)
Some time in the coming decade, Iran will probably acquire nuclear weapons or the capacity to quickly produce them. This monograph provides a midterm strategy for dealing with Iran that neither begins nor ends at the point at which Tehran acquires a nuclear weapon capability. It proposes an approach that neither acquiesces to a nuclear-armed Iran nor refuses to admit the possibility--indeed, the likelihood--of this occurring.